Dampak Tumpang Tindih Bahasa Ibu Dalam Perkembangan Bahasa Anak - Ajeng Priendarningtyas (UIN Sultan Maulana Hasanudin Banten, 2022)
This study aims to collaborate theory with practice that occurs in the field, also knowing that the use of mother tongue in early childhood is very important. The research method used is descriptive qualitative with literature study in the form of photos, notes, and books. The results of this study are the occurrence of overlap in language development in children is very influential and has an impact on self and communication. The stimulation given cannot be instant but is carried out continuously. Because the child's grasping power will adjust how the language is given so that what kind of reinforcement will be generated. The use of mother tongue that is not optimal will cause language overlap. The occurrence of overlaps can result in difficulties in developing children's language development in everyday life; such as to communicate and interact with other people and the environment, impaired concentration, and unstable behavior.